PERAN DAN UPAYA GURU DALAM PENERAPAN PENDIDIKAN KARAKTER PADA PEMBELAJARAN SEJARAH DI SMA NEGERI 2 BONE - Muh Akbar; Apriyani Putri Rezeki; Bahri Bahri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
Character education is one of the most important things in the world of education and is interesting to study in more depth, especially in history learning. This research aims to determine: The role and efforts of teachers in implementing character education in history learning at SMA Negeri 2 Bone. This research uses a qualitative method with an analytical descriptive approach. Qualitative research is research that has a descriptive basis. This research aims to understand or reveal the problem in depth. This research requires two data sources to complete the research data, the sources needed are primary and secondary sources. Data collection techniques were carried out using observation methods, interview methods and documentation methods. Data analysis in this research uses intertwining or flowing analysis (Flow Model Analysis). The results of this research show: Teachers have a very strategic role in cultivating character education in history learning. Apart from that, teachers have a role as motivators for students. The efforts made are: planning stages, implementation by creating lesson materials, learning strategies, and learning media, finally the evaluation stage.